Differences in clinical practice regarding screening and treatment of infections associated with spontaneous preterm birth: An international survey. (November 2021) - Werter, Dominique E.; Dehaene, Isabelle; Gurney, Leo; Vargas Buján, Mireia; Kazemier, Brenda M.
Highlights: Lack of evidence on screening for and treatment of infections associated with preterm birth. Screening for infections associated with preterm birth differ between European countries. Treatment for infections associated with preterm birth differ between European countries. Abstract: Objective: An association between infections in pregnancy and increased risk of preterm birth (PTB) is described in the literature. We anticipated that differences may exist in screening and treatment approaches for infections associated with PTB, within and between European countries. The aim of this study was to examine and analyse these differences in clinical practice in greater detail. Study Design: We created a descriptive survey examining the screening and treatment of infections in pregnancy. The survey was sent to European representatives of the International Spontaneous Preterm Birth Young Investigators (I-SPY) group in Europe, who sent it to their network. Finally, we had 50 respondents from ten European countries. Results: We found substantial differences in screening for bacterial vaginosis and asymptomatic bacteriuria, administration of antibiotics to women with preterm prelabour rupture of membranes (PPROM), and timing of induction of labour after PPROM. These differences in clinical practice were present both within, and between countries. Conclusions: Approaches for screening and treatment of infections associated with PTB differ between European countries. There is a lack of robust evidence, which is reflected in a lack of uniformity in international guidelines. International collaboration is paramount to enlarge sample sizes in obstetric studies and to facilitate the process of developing, updating, and implementing consistent guidelines across Europe and beyond.